Peran sektor basis dalam mengurangi disparitas pendapatan di Kawasan Subosukawonosraten Provinsi Jawa Tengah - Dinda Larasati; Riko Setya Wijaya (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study aims to analyze the economic base sector and the role of economic base sector in reducing in income disparity between regencies/cities in Subosukawonosraten region, regional typology, and knowing the level of disparity income in the Subosukawonosraten region by using Location Quotient, Williamson Index and Klassen Typology. The results showed that The Subosukawonosraten area has 12 economic base, and the most dominant sector reduce the income disparity is transportation and warehousing sector (1.8626%); Klassen Typology showed that only 1 city are included in the quadrant category II, which is a developed but depressed area, 4 regencies/cities are included in quadrant III or regions developing fast and 2 regencies/cities are included in undeveloped areas; Williamson index in timeframe 4 years tends to increase from 0.37441743 in 2017 to 0.402990835 in 2020.